Using State Child Labor Laws to Identify the Effect of School‐Year Work on High School Achievement - Tyler, John H. (Journal of Labor Economics, 2003)
This article uses variation in the labor supply of twelfth‐grade students created by interstate variations in child labor laws to estimate the effect of school‐year work on twelfth‐grade math achievement. The instrumental variable estimates in this article indicate that an exogenous decrease in school‐year hours worked of 10 hours per week would result in a 0.2 standard deviation increase in math scores. Comparisons to ordinary least squares estimates suggest that failure to account for the endogeneity of the labor supply decisions of high school students will result in underestimates of the negative impact of school‐year work on academic achievement.